Implementasi Kebijakan Penyaluran Bantuan Pemerintah Bagi Pelaku Usaha Mikro Di Kelurahan Pasirwangi Kecamatan Ujungberung Kota Bandung - Nurhadi, Nurhadi; Kania, Ikeu; Mulyaningsih, Mulyaningsih (Ministrate: Jurnal Birokrasi dan Pemerintahan Daerah, 2025)
The implementation of the Micro Business Productive Assistance (BPUM) policy in Pasirwangi Village, Ujungberung District, Bandung City faces various challenges that hinder its effectiveness. This study aims to analyze the main causes that impact the implementation of the policy, especially in terms of communication, resources, implementer disposition, and bureaucratic structure. Using a qualitative approach and case study method, data were collected through observation and interviews with government officials and BPUM recipients. The results of the study indicate that ineffective communication between the government and beneficiaries causes misinformation and procedural confusion. Limited human resources, especially the lack of competent enumerators, have an impact on the inefficiency of public services. In addition, the less than optimal implementer disposition, such as the low readiness and responsiveness of village officials, further weakens the implementation of the policy. An inconsistent bureaucratic structure, with frequent changes in procedures without adequate coordination, also hinders the distribution of assistance. To improve the effectiveness of BPUM, this study recommends standardization of operational procedures, improvement of coordination mechanisms, and utilization of digital technology in administration and policy transparency. Strengthening the capacity of the apparatus through continuous training and the establishment of a comprehensive monitoring and evaluation system is also an important step. It is hoped that this effort can increase policy efficiency, support the recovery of micro businesses, and improve community welfare in a sustainable manner.